Digital communication, brand reputation and training - Morales, Hermes A.J; Greco, Francesca (Community Notebook. People, Education and Welfare in the Society 5.0, 2024)
Companies promote their image by communicating, internally and externally, news about planned training events. This promotional activity is very important because it enables effective communication with their publics aimed at fostering the organisation’s brand reputation. Training, in fact, reveals itself as a strategic asset to promote both employee development and culture outside the company boundaries. This study starts from the hypothesis that the organisational culture that guides training can be explored precisely from the communication on digital platforms that the company produces on the subject. Understanding the cultural frameworks that substantiate public relations would not only allow us to understand how the organisation thinks about the development of its own resources and those of the territory, but could constitute substantial information to orient training within it.